Nuevos registros de Elaphoglossum (Dryopteridaceae) para el Neotrópico (2012)
ABSTRACT: The geographic distributition of ten species of Elaphoglossum are expanded in the Neotropics: E. adrianae, E. bakeri, E. chloödes, E. delgadilloanum, E. furfuraceum, E. lonchophyllum, E. obtusum, E. praetermissum, E. pseudoherminieri, and E. subciliatum, as result of recent revisions of specimens in the herbaria HUA, US, and VALLE, and from consulations of type material in several herbaria such as CR, F, K, MO, NY, and US. Of the species listed, nine species are reported from Colombia, two from Venezuela, and one from Ecuador.